Climate change mitigation potential of rural households in Chattogram District of Bangladesh - Haque, Md. Zeesun-Ul; Islam, Thuhidul; Baul, Tarit Kumar; Kilpeläinen, Antti; Alam, Ashraful; Jashimuddin, Mohammed; Kar, Shiba P. (Springer Nature, 2025)
A holistic analysis of climate change mitigation potential at the household level has not yet been conducted in Bangladesh. We aimed to quantify the climate change mitigation potential of carbon storage in homegarden trees and wooden furniture across households of different income levels in Anowara Upazila, Chattogram, Bangladesh. We also quantified the substitution potential of wooden furniture and use of renewable energy sources. Following simple random techniques, we surveyed a total of 217 homegardens and their respective households from the three villages of Boirag Union, with a sampling intensity of 5%. Furniture manufacturers were also surveyed to determine the typical amount of wood and types of tree species used for furniture. We found that homegarden trees stored on average 42 Mg CO2 per hectare, and most carbon was found in Albizia lebbeck, Tectona grandis, Acacia auriculiformis, and Swietenia macrophylla. Carbon storage and substitution benefits of wooden furniture were significantly (p<0.05) higher in the upper-middle (2.07 and 2.32 Mg CO2 household−1 year−1) than in the lower-middle (1.2 and 1.34 Mg CO2 household−1 year−1) income group. Households in the upper-middle income group generated higher emissions from combusting fossil fuels (electricity and LPG) than those in the lower-middle income group. These emissions could be avoided by using improved cooking stoves and biogas obtained from kitchen waste, poultry waste, and cowdung. The emission reduction potential of using biogas was significantly (p<0.05) higher in the upper-middle (2.43 Mg CO2 household−1 year−1) than in lower-middle group (1.87 Mg CO2 household−1 year−1). The research findings suggest that implementing sustainable management and low carbon practices in households can significantly contribute to climate change mitigation by intervening policy mechanisms, while offering carbon farming techniques as well as a carbon market.
Keywords: homegarden trees; wooden furniture; carbon storage; displacement factors; fossil counterparts; substitution potential